Detection of carotenoids of halophilic prokaryotes in solid inclusions inside laboratory-grown chloride and sulfate crystals using a portable Raman spectrometer: applications for Mars exploration - Culka, Adam; Košek, Filip; Oren, Aharon; Mana, Lily; Jehlička, Jan (FEMS microbiology letters, 2019)
Inclusions in evaporitic minerals sometimes contain remnants of microorganisms or biomarkers, which can be considered as traces of life. Raman spectroscopy with resonance enhancement is one of the best analytical methods to search for such biomarkers in places of interest for astrobiology, including the surface and near subsurface of planet Mars. Portable Raman spectrometers are used as training tools for detection of biomarkers. Investigations of the limits and challenges of detecting biomolecules in crystals using Raman spectroscopy is important because natural occurrences often involve mineral assemblages as well as their fluid and solid inclusions. A portable Raman spectrometer with 532 nm excitation was used for detection of carotenoid biomarkers: salinixanthin of Salinibacter ruber (Bacteroidetes) and α-bacterioruberin of Halorubrum sodomense (Halobacteria) in laboratory-grown artificial inclusions in compound crystals of several chlorides and sulfates, simulating entrapment of microorganisms in evaporitic minerals. Crystals of halite (NaCl), sylvite (KCl), arcanite (K2SO4) and tschermigite ((NH4)Al(SO4)2·12H2O) were grown from synthetic solutions that contained microorganisms. A second crystalline layer of NaCl or K2SO4 was grown subsequently so that primary crystals containing microorganisms are considered as solid inclusions. A portable Raman spectrometer with resonance enabling excitation detected signals of both carotenoid pigments. Correct positions of diagnostic Raman bands corresponding to the specific carotenoids were recorded.
Keywords: Carotenoids; Crystallization; chloridy; Ramanova spektroskopie; sírany; Sulfates; Exobiology; krystalizace; Prokaryotic Cells; Spectrum Analysis, Raman; karotenoidy; Bacteria; Mars; prokaryotické buňky; exobiologie; Chlorides